A CONSTRATIVE STUDY OF ‘MAKE’ VERB IN ENGLISH AND ‘HABU’ VERB IN MUNANESE LANGUAGE - Yetty Yetty; Saiful Latif (FKIP Universitas Khairun, 2022)
The aims of this study was to investigate the similarities and differences of ‘make” verb in English and ‘habu’ verb in Munanese language in terms of semantics and grammar construction. The data of this study consisted of English data which collected from Corpus of Contemporary American English (COCA) and Munanese language data that obtained from field research through process of observation and in-depth interview. Both of the data were analyzed by descriptive and qualitative analysis. The result showed that semantically,’make’ verb and ‘habu’ verb apply similar meaning that refers to ‘to create or prepare something by combining materials or putting parts together; to cause something to exist happen’. The differences of two verbs are on the grammatical construction. The verb ‘make’ is applied in construction VII. The interesting thing that ‘make’ verb also can be appied in variant construction VIIb (the variant which is not stated in the Dixon’s theoritical framework) based on COCA data. Meanwhile, the construction applied in habu verb is also construction VII, and some extra variant which is aso not stated in Dixon’s theory. Furthermore, ‘habu’ verb can be applied in Giving verb semantic role. As the main point, it is proved that the variety of language is determined of cutural background.